Confinement Induced First Order Crystallization Kinetics for the Poly(ethylene oxide) Block within A PEO‐b‐PB Diblock Copolymer Infiltrated within Alumina Nano‐Porous Template. Issue 1 (March 2014) - Michell, Rose Mary; Blaszczyk‐Lezak, Iwona; Mijangos, Carmen; Müller, Alejandro J.; Klumperman, Bert; Mallon, Peter; Pasch, Harald; van Reenen, Albert
Summary We report homogeneous nucleation and first order crystallization kinetics for the PEO block within a PEO‐b‐PB diblock copolymer infiltrated within alumina nanopores. For the highly confined heterogeneity free PEO block nano‐domains, the overall crystallization kinetics is dominated by nucleation and therefore becomes first order. The nucleation mechanism changes from heterogeneous nucleation for the PEO block within the uninfiltrated copolymer (since it has a composition with 79% PEO that conforms a percolated matrix) to homogeneous nucleation for confined and isolated heterogeneity free nanodomains.